Effect of Nb5+ Doping on the Structure and Electrochemical Performances of LiFePO4. (March 2019) - Chen, Lin; Lu, Cheng; Yin, Shuo; Wang, Meng; Wang, Yiqiao; Liu, Hui; Ren, Yongzhi; Zuo, Lingli; Guo, Caiyu; Zhang, Yang; Chen, Yunbo
Abstract: Nb-doped Lix Nb0.005 Fey PO4 /C cathode material for lithium-ion batteries were prepared by two-fluid spray-drying using FePO4 ·2H2 O, LiOH·H2 O, C6 H12 O6 (glucose) as raw materials under N2 atmosphere. The effects of doping Nb 5+ on the structure, morphology and electrochemical performances of LiFePO4 were investigated. The results show that Lix Nb 0.005 Fey PO4 /C has Olivine Structure and pure phase. The Lix Nb0.005 Fey PO4 /C had an initial discharge specific capacity of 158.5mAh/g at 0.1C and its specific capacities were 109mAh/g at 5C. The initial charge/discharge efficiency reached 93.9%. The discharge specific capacity of the Lix Nb0.005 Fey PO4 /C at 253K is 82.2mAh/g. This investigation suggests that the Nb 5+ doped material possess high rate capability and excellent low temperature electrochemical performance.